```(dz)/(dx) = 1/sqrt(x^2 + y^2) (d/(dx) sqrt(x^2 + y^2))`

since `d/(dx) ln(f(x)) = (f'(x))/f(x)`

`d/(dx) sqrt(x^2 + y^2) = (1/2)(x^2+y^2)^(-1/2)(2x) = x/sqrt(x^2+y^2)`

So we have

`(dz)/(dx) = 1/(sqrt(x^2+y^2))(x/sqrt(x^2+y^2)) = x/(x^2+y^2)`

By the symmetry of the function `z = ln(sqrt(x^2+y^2))` ,

`(dz)/(dy) = y/(x^2+y^2)`

`therefore` `y ((dz)/(dx)) + y((dz)/(dy)) = x^2/(x^2+y^2) + y^2/(x^2+y^2) = 1`

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now